2013
DOI: 10.1016/j.bbr.2013.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Role of insular cortex D1 and D2 dopamine receptors in nicotine self-administration in rats

Abstract: The insular cortex has been associated with the processing of rewarding stimuli and with the neural bases of drug addiction. Ischemic damage to the insula has been associated with decreased desire to smoke cigarettes. Which component of insular function is involved in the neural basis of cigarette smoking is not clear. Dopamine systems are crucial for the reinforcing value of addictive drugs. The DA projection from the ventral tegmental area to the nucleus accumbens (NAc) has been shown to be a vital pathway f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 37 publications
4
31
0
Order By: Relevance
“…When examining the incubation enhanced cue-induced reinstatement of nicotine seeking, Abdolahi and colleagues (2010) observed an associated increase in the dopamine and cAMP-regulated phosphoprotein of 32 kDa (DARPP-32), a phosphoprotein enriched in neurons containing dopamine D1-subtype receptors, specifically within the RAIC but not the CGIC of rats [31]. Confirming the ability of direct RAIC manipulation to affect nicotine self-administration, Kutlu and colleagues (2013), found that bilateral infusions of D1, but not D2, antagonists into the RAIC were capable of decreasing nicotine self-administration in rats [16] similar to the effect found with GABA agonist-induced inactivation in the present study.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…When examining the incubation enhanced cue-induced reinstatement of nicotine seeking, Abdolahi and colleagues (2010) observed an associated increase in the dopamine and cAMP-regulated phosphoprotein of 32 kDa (DARPP-32), a phosphoprotein enriched in neurons containing dopamine D1-subtype receptors, specifically within the RAIC but not the CGIC of rats [31]. Confirming the ability of direct RAIC manipulation to affect nicotine self-administration, Kutlu and colleagues (2013), found that bilateral infusions of D1, but not D2, antagonists into the RAIC were capable of decreasing nicotine self-administration in rats [16] similar to the effect found with GABA agonist-induced inactivation in the present study.…”
Section: Discussionmentioning
confidence: 87%
“…Within animal studies involving insular cortex manipulations, studies have demonstrated both a role for the CGIC [14,15,17,41,42] or RAIC [16,[43][44][45][46][47] or both [13,48] in addiction relevant behaviors. To our knowledge, only two studies thus far have compared manipulations of the CGIC vs. RAIC and found differential involvement in addiction-relevant behaviors.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Primary location of DA neuron activity is measured in the ventral striatum and midbrain, but DA-mediated brain activation is also distributed across the prefrontal cortex, including the insula. 14 Within the brain reward circuitry DA has the role of responding to unexpected receipt or omission of rewards, acts as a learning signal and guides us to approach rewarding stimuli, including food. 9,15 Thus, the DA system could be involved in altered food approach or food avoidance in individuals with anorexia nervosa.…”
Section: Introductionmentioning
confidence: 99%